SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN LAPTOP DENGAN MENERAPKAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) - Nathaniel, Darwin; Padli Pratama, Fery; Farhan, Muhammad; Asido Elyakim P, Victor (Yayasan Nuraini Ibrahim Mandiri, 2024)
This research aims to develop a Decision Support System (SPK) using the Simple Additive Weighting (SAW) method in selecting the best laptop based on various criteria. The criteria used in this research include price, RAM, internal memory, screen size, and processor. The SAW method was chosen because of its ability to handle multi-criteria decision making by giving weights to each criterion and calculating the final score of each alternative through data normalization. The results showed that the five best laptop alternatives with the highest scores were HP SPECTRE X360 with a score of 75.00, Xiaomi RedmiBook 15 with a score of 72.50, ASUS Zenbook S 13 OLED with a score of 67.50, Lenovo Thinkbook 14 with a score of 67.00, and Huawei MateBook D14 with a score of 67.00. From these results, HP SPECTRE X360 was declared the best choice. This study concludes that the SAW method is effective in helping decision making involving many criteria and alternatives. The weights of criteria such as price and processor show a significant influence on the final result. For further research, it is recommended to evaluate more deeply the determination of weights and normalization formulas to improve decision accuracy. Thus, this method can be adapted to a wider context and relevant in complex decision making